The anguish of snails : Native American folklore in the West - Toelken, Barre, 1935-2018 (Folklife of the West, 2003)
After a career of working and living with Native Americans and studying their traditions, Barre Toelken has written this sweeping study of Native American folklore in the West. Within a framework of performance theory, cultural worldview, and collaborative research, he examines Native American visual arts, dance, oral tradition (story and song), humor, and patterns of thinking and discovery to demonstrate what can be gleaned from Indian traditions by Natives and non-Natives alike. In the process he considers popular distortions of Indian beliefs, demystifies many traditions by showing how they can be comprehended within their cultural contexts, considers why some aspects of Native American life are not meant to be understood by or shared with outsiders, and emphasizes how much can be learned through sensitivity to and awareness of cultural values.